Profile Hemodynamics (Blood Pressure And Heart Rate) Changes in The Use of Adrenaline in Cesarean Section With Spinal Anesthesia at Dr Soetomo Surabaya Hospital - Ainur Rahmah; Arie Utariani; Achmad Basori (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: spinal anesthesia block is one of anesthesia technique that  aims to block motor nerves resulting in paresis or anesthesia and paralysis or loss of muscle function in myotomes that are the same level as blocked dermatomes. Caesarean section is one of the surgical actions that are often performed mainly in birth cases. Besides that, the mechanism of the effects of giving birth to the operation of type B autonomic caesarean section autonomic nerve pronglion nerve which results in a decrease in the resistance of peripheral veins and peripheral vasodilatation which results in an imbalance in hemodynamics especially in blood pressure and heart rate and cause of hypotension. Vasopressor, fluid therapy, vasoconstrictor are given to reduce the toxicity of local anesthesia and to overcome hypotension. Objective: To determine hemodynamic changes (blood pressure and pulse) in spinal anesthesia block surgery patients with caesarean section at Dr Soetomo Hospital. Material and Method: This research is descriptive with a retrospective from January - March 2018, the sample taken with total sampling from secondary data from the central medical record at RSUD Dr. Soetomo. Results and Discussion: 68 samples were obtained from inclusion and exclusion criteria there was a change in blood pressure and pulse in patients with caesarean section with spinal anesthesia block with the addition of vasoconstrictors. There was a decrease in average systolic pressure 13.25, diastole 18.25 and pulse 4.5 and in no increase. There was a decrease in average systolic pressure 11.9286, diastole 13.8929 and pulse 5.6429 and no addition of p> 0.05 the two are not significantly different. Conclusion: addition of adrenaline to spinal anesthesia in caesarean section patients was not cause significant hemodynamic (blood pressure and heart rate) changes.